CORRECTION OF DISCARDED HMITS OF AUTOMATIC LINE OF SORTING BY PROCESSIBILITY OF NON-TUMED CASTINGS OF NIPPLES OF MALLEABLE CAST IRON KCh30-6 AT CHANGING OF THEIR SIZES - S. G. Sandomirski; V. A. Vershinin (Литьë и металлургия)
The methods of correction of rejected limits of automated control line and automated sorting on processibility of unturned nipple castings of malleable cast iron KCh 30-6 on the basis of devices M axi-P is developed and implemented in production of Minsk plant of heating equipment.